Giving Banana ‘Raja’ Peel Extract (Musades Paradisiaca Sapientium) After Moderate Intensity Training Reduces MDA Levels In Rats - Andarianto, Andre; Pranoto, Adi; Sandy, Berliana Dwi Nandita; Kinanti, Rias Gesang; Yunus, Mahmud (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The study design was the randomized posttest-only group design, 24 tails, male Rattus Norvegicus Strain Wistar, 8 weeks, 160±20 grams and randomly divided into 4 groups. K1 (n=6, moderate intensity exercise, treadmill with a speed of 14-16 m/min for 15-30 minutes), K2 (n=6, moderate intensity exercise + giving Raja Banana peel extract, treadmill with a speed of 14-16 m/min for 15-30 minutes), K3 (n=6, high intensity exercise, treadmill at a speed of 22-25 m/min for 10-20 minutes) and K4 (n=6, high intensity exercise + giving Raja Banana peel extract, treadmill with a speed of 22-25 m/min for 10-20 minutes). The training interventions were conducted at 17.00-21.00 p.m with a frequency of 7 times/week for 8 weeks. The blood was drawn 12 hours after the last exercise intervention. it is concluded that giving Raja Banana peel extract after moderate and high intensity exercise reduced MDA levels in rats.